2016
DOI: 10.12816/0028466
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Cash Holding and the Financial Crisis : Evidence from Jordan = قيمة النقد المحتفظ به و الأزمة المالية : دليل من الأردن

Abstract: This research has investigated the effect of the recent financial crisis on the value of cash holding among a sample of 80 non-financial listed firms from Jordan during the period 2001-2011. Using fixed-effect panel data analysis, the study has shown that cash is valued at a discount in Jordan since the corporate governance system is weak, investors have poor protection, and free cash flow and agency problems exist. As a result of the financial crisis, external financing has become more difficult and expensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…This result is inconsistent with some studies conducted in Jordan. example, Alzoubi (2016) offered evidence that ROA was significantly and negatively associated with DAC, while Al Qallap (2014) found no significant relationship between ROA and DAC. The IDUS variable was negatively and significantly related to DAC in all models, which indicates that companies in the industrial sector had a lower positive DAC than those companies in the service sector.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is inconsistent with some studies conducted in Jordan. example, Alzoubi (2016) offered evidence that ROA was significantly and negatively associated with DAC, while Al Qallap (2014) found no significant relationship between ROA and DAC. The IDUS variable was negatively and significantly related to DAC in all models, which indicates that companies in the industrial sector had a lower positive DAC than those companies in the service sector.…”
Section: Discussionmentioning
confidence: 99%
“…Alqatamin et al (2017) documented similar findings with a mean of DAC of 0.097. Alzoubi (2016) concluded that the mean of the absolute value of DAC was 9.3 per cent, which indicates that, on an average, the managers of the listed companies on ASE practised earnings management. Finally, Kanakriyah et al (2017) found that public companies in Jordan manipulated the reported earnings at a high level with a mean of 3.772.…”
Section: An Overview Of the Amman Stock Exchangementioning
confidence: 99%
See 1 more Smart Citation
“…The existing cash policy in a company is also closely related to the access that can be obtained by the company in obtaining funding sources other than internal funding and the business environment faced by the company (Pinkowitz et al, 2006;Faulkender and Wang, 2006;Dittmar and Mahrt-Smith, 2007;Kalcheva and Lins, 2007;Harford et al, 2008;Fresard and Salva, 2010;Haw et al, 2011;Tong, 2011;Alzoubi, 2013;2015 and2016).…”
Section: Introductionmentioning
confidence: 99%